Manajemen Pembelajaran Program P5PPRA di Madrasah Ibtidaiyah - Sofya, Ayu; Novita, Nursyahbani Chusnul; Wigati, Indah (Universitas Islam Negeri Raden Fatah Palembang, 2025)
The Pancasila and Rahmatan Lil Alamin (P5PPRA) student profile strengthening program with the theme